Membangun Kreatifitas Melalui Pembuatan Dompet Dengan Tali Kur Bagi Ibu-Ibu Dusun Sukadamai Desa Madukoro Baru - Rulik Setiani; Davin Ramadhani; Muhammad Cakal Cendikia; Putri Afifah Daina Angraini; Ulfa Arma Putri; Hasmillah Ilhami (JCSE: Journal of Community Service and Empowerment, 2023)
Community service activities carried out in Madukoro Baru Village, North Kotabumi District, North Lampung Regency, Lampung Province on 1–28 February 2023, the activity of making wallets using a rope was carried out as a form of community creativity in Sukadamai hamlet with the aim of increasing the creative economy and business development, the aid team to the people of Muhammadiyah University Kotabumi saw that in the village of Madukoro Baru there was a need for direction so that many people would be interested in coming to the village of Madukoro Baru because there was no tourism in that village so with this activity the team hoped that the village of Madukoro Baru would be able to attract the interest of people outside the village of Madukoro Baru and enliven the village by learning together. The implementation method is carried out with the community service team demonstrated how to make rope kur wallets as well as residents, especially mothers who are involved in this activity. With this activity, it is hoped that it can increase the creative economy in the handicraft sector as an effort to build the family economy in particular and the village economy in general.